UJI EFEKTIVITAS ANTIBIOTIK EKSTRAK DAUN BELIMBIMG WULUH (AVERRHOA BILIMBI L) DAN EKSTRAK HABATUSSAUDA (NIGELLA SATIVA L) TERHADAP JUMLAH LEUKOSIT MENCIT JANTAN (MUS MUSCULUS L) YANG TERINFEKSI STAPHYLOCOCCUS AUREUS - SIGIT KURNIAWAN; YENITA . (JURNAL ILMIAH KOHESI, 2021)
Infectious disease is a disease caused by microorganisms that attack host, one of which is skin infection by Staphylococcusaureus. Some types of diseases that can be caused by Staphylococcus aureus infections are pyoderma, nosocomialinfections, infections of wounds, food poisoning, and toxic shock syndrome. Indonesian people have long been applyingtraditional medicine, using plants that are believed to be efficacious to treat diseases. Plants that can be used as traditionalmedicine are leaves of starfruit and habatussauda starfruit. Based on previous research, this plant contains compounds thatare as antibacterial. To determine the effectiveness of antibiotic extract of starfruit leaf extract (Averrhoa bilimbi L) withhabatussauda extract (Nigella sativa L) on the number of leukocytes in male mice (Mus musculus L) infected withStaphylococcus aureus. This study is an experimental study with a Post test with Control Group Design method. Mice weredivided into 6 groups namely K (-), K (+), P1, P2, P3 and P4 with a total sample of 6 groups. All mice were cut on the backand infected with Staphylococcus aureus. Administered orally by force-feeding. Based on the results of hypothesis testingwith the Kruskal Walis test p value = 0.007 (p <0.05), there were significant differences in the number of leukocytes in the 6study groups. There was a difference in effectiveness in reducing the number of leukocytes in male mice infected withStaphylococcus aureus in the treatment group. Group K (+) is the most effective group to reduce the number of leukocytes.Then followed by groups P4, P3, P2 and P1.